2016
DOI: 10.9724/kfcs.2016.32.5.600
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Sensory Characteristics, and Microbial Safety of Sunsik with Fermented Turmeric Powder

Abstract: Purpose: To investigate the antioxidant, physicochemical sensory, and microbial safety qualities of sunsik containing fermented Curcuma longa L. powder. Methods: Quality characteristics of samples were measured using pH, moisture content, crude ash content, color and sensory evaluation. Antioxidant activities of samples were compared using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)(ABTS) cation radical scavenging activities. Microbial saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the Literature there are only some works, report the addition of turmeric in bakery products such as butter cake (Lean and Mohamed, 1999), cookies (Choi et al, 2013;Ju and Hong, 2011), cakes (Park et al, 2012), Yaksik (Min and Hwang, 2017), snack of rice (Lim and Han, 2016) and bread (Lim et al, 2011;Jeon et al, 2013;Jung et al, 2014), although there are other reports using turmeric powder in food products such as Noodles (Garakguksu) (Song and Jung, 2009), jeung-pyun (Shin et al, 2018), pyeonyuk (Bae et al, 2018), sunsink (Wu et al, 2016), etc. In the case of rice snack, the authors shown that the turmeric snacks lengthen the shelf life of the product and in the butter cake, the authors reported antimycotic effect of the turmeric.…”
Section: Introductionmentioning
confidence: 99%
“…In the Literature there are only some works, report the addition of turmeric in bakery products such as butter cake (Lean and Mohamed, 1999), cookies (Choi et al, 2013;Ju and Hong, 2011), cakes (Park et al, 2012), Yaksik (Min and Hwang, 2017), snack of rice (Lim and Han, 2016) and bread (Lim et al, 2011;Jeon et al, 2013;Jung et al, 2014), although there are other reports using turmeric powder in food products such as Noodles (Garakguksu) (Song and Jung, 2009), jeung-pyun (Shin et al, 2018), pyeonyuk (Bae et al, 2018), sunsink (Wu et al, 2016), etc. In the case of rice snack, the authors shown that the turmeric snacks lengthen the shelf life of the product and in the butter cake, the authors reported antimycotic effect of the turmeric.…”
Section: Introductionmentioning
confidence: 99%